Pengaruh IPM, Pertumbuhan Ekonomi, dan Pengangguran terhadap Kemiskinan Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2017-2019 - Nuraeni Handayani (Diponegoro Journal of Economics, 2022)
Central Java Province is a province with a poverty rate percentage that ranks second in Java after DIY, but the poverty rate in Central Java Province is still quite high because it is still above the national poverty rate. This study aims to analyze the effect of the Human Development Index (HDI), economic growth and unemployment rates in districts/cities in Central Java Province in 2017-2019. Based on the data used, in this study using panel data regression analysis with the fixed effect method which was tested using the Eviews 9.0 application. The data used in this study is secondary data. The independent variables used in this study are the Human Development Index (HDI), economic growth and unemployment rates, while the dependent variable used is the poverty rate in 35 regencies/cities in Central Java Province in 2017-2019. The results of this research that the Human Development Index (HDI) had a positive effect on the poverty rate in districts/cities in Central Java Province in 2017-2019. Variables of economic growth and unemployment had no significant effect on the poverty rate. The variables of the Human Development Index (HDI), economic growth and the unemployment rate together have a significant effect on poverty in Central Java Province in districts/cities in Central Java Province in 2017-2019.